Why Riders Perform Risky Riding Behavior in Jakarta: The effects of Hazardous Situations and Gender on Risk Perception - Maulina, Dewi; Danilasari, Keyni Regina; Nazhira, Fara; Jufri, Satara Samia (Psychological Research on Urban Society, 2018)
The relationship between risky riding behavior and traffic accidents has been identified in previous research. However, there is limited research that focuses on the interaction between internal and external factors and the effect this has on riders’ risky riding decisions. The aim of this study is to examine the effect of hazardous situations and gender on risk perception and risky riding behavior among motorcyclists. We focus on lane-splitting behavior as one of the most common risky riding behaviors among motorcyclists in Jakarta. A 2×2 mixed-groups factorial ANOVA (hazardous situation × gender) was conducted with 72 participant riders, male as well as female. Participants were asked to read different scenarios and watch six video clips that showed pro-risk and anti-risk hazardous situations. At the end of each clip, participants answered questions related to risk perception and lane splitting decisions. Results show that hazardous situations have a significant effect on each dimension of risk perception and on risky riding behavior. However, results suggest that gender has a significant effect only on two dimensions of risk perception, namely, efficacy and worry and insecurity. We also found a significant effect of the interaction between hazardous situations and gender on risk perception, which is the dimension of the likelihood of an accident. Based on the results of this study, it can be concluded that it is important for law enforcement to consider the role of risk perception when granting motorcycle licenses.